A matheuristic for a multi-period three-echelon network design problem with temporary capacity acquisition - Correia, Isabel (2024)
This support is gratefully acknowledged. We also thank the anonymous reviewers for their valuable comments. Publisher Copyright: © 2024 The Author(s)